2017
DOI: 10.1002/humu.23310
|View full text |Cite
|
Sign up to set email alerts
|

PAX7mutation in a syndrome of failure to thrive, hypotonia, and global neurodevelopmental delay

Abstract: PAX7 encodes a transcription factor essential in neural crest formation, myogenesis, and pituitary lineage specification. Pax7 null mice fail to thrive and exhibit muscle weakness, dying within 3 weeks. We describe a human autosomal-recessive syndrome, with failure to thrive, severe global developmental delay, microcephaly, axial hypotonia, pyramidal signs, dystonic postures, seizures, irritability, and self-mutilation. Aside from low blood carnitine levels, biochemical and metabolic screen was normal, with gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…Paxbp1 was originally identified as a Pax7binding protein in the mouse (26). Interestingly, two recent clinical studies reported homozygous mutations in human PAXBP1 and PAX7 that are linked to similar human genetic disorders with global developmental delay and myopathic hypotonia (64,65). Are the defects of Paxbp1-null ASCs linked to Pax7?…”
Section: Discussionmentioning
confidence: 99%
“…Paxbp1 was originally identified as a Pax7binding protein in the mouse (26). Interestingly, two recent clinical studies reported homozygous mutations in human PAXBP1 and PAX7 that are linked to similar human genetic disorders with global developmental delay and myopathic hypotonia (64,65). Are the defects of Paxbp1-null ASCs linked to Pax7?…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from both parents' lymphocytes using GENzol Tri RNA Pure Kit (Geneaid Biotech) according to manufacturer’s instructions. qRT-PCR was performed as previously described 16. Primer sequences will be provided on request.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as previously described 16. Protein lysates were extracted from wild-type and SEC31A KO HEK293T cells.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of Pax7 is extensive, since it is detected in mesencephalon, rhombencephalon, dorsal NT, fronto-nasal region and NCCs that migrate from the dorsal region of the NT to the pharyngeal arches (Betters et al, 2010;Murdoch et al, 2012). A mutation of Pax7 (isoform 3) was recently found in patients, causing a phenotype of neurodevelopmental delay during development and promoting microcephaly, irritability and self-mutilation among others symptoms (Proskorovski-Ohayon et al, 2017). Therefore, Pax7 is a crucial gene in the induction of NC and in its migration.…”
Section: Pax Familymentioning
confidence: 99%